2012
DOI: 10.3892/ijo.2012.1359
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin enhances doxorubicin-induced apoptosis and reduces tumor growth in human hepatocellular carcinoma cells in vitro and in vivo

Abstract: Abstract. Combined therapy with multiple drugs is a common practice in the treatment of cancer, which can achieve better therapeutic effects than a single drug, and can reduce the side effects as well as drug resistance. This study aimed to determine whether aspirin (ASA) shows synergism with doxorubicin (DOX) in HepG2 human hepatocellular carcinoma cells in vitro and in a HepG2 cell xenograft model in BALB/c nude mice. When treated in combination, DOX (0.25 nmol/ ml) and ASA (5 µmol/ml) produced strong synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…While not statistically significant, the treatment of tumors derived from A549 cells with doxorubicin resulted in a small effect (Cohen’s d = 0.51 [−0.62, 1.63]), which is in the expected direction. A small reduction in tumor weight compared to vehicle control has also been reported in other studies that utilized a similar low dose doxorubicin experimental design (Biswas et al, 2013; Hossain et al, 2012; Lopez et al, 2009; Wang et al, 2010).
10.7554/eLife.17044.004Figure 2.Final tumor weights from xenograft experiment testing efficacy of cimetidine in inhibiting the growth of tumors in SCID mice.At the end of the predefined study period (Day 12), tumors from the xenograft experiment reported in Figure 1 were excised and weighed.
…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…While not statistically significant, the treatment of tumors derived from A549 cells with doxorubicin resulted in a small effect (Cohen’s d = 0.51 [−0.62, 1.63]), which is in the expected direction. A small reduction in tumor weight compared to vehicle control has also been reported in other studies that utilized a similar low dose doxorubicin experimental design (Biswas et al, 2013; Hossain et al, 2012; Lopez et al, 2009; Wang et al, 2010).
10.7554/eLife.17044.004Figure 2.Final tumor weights from xenograft experiment testing efficacy of cimetidine in inhibiting the growth of tumors in SCID mice.At the end of the predefined study period (Day 12), tumors from the xenograft experiment reported in Figure 1 were excised and weighed.
…”
Section: Resultssupporting
confidence: 74%
“…Additionally, mice treated with doxorubicin started to lose weight and had a rough coat starting on approximately day 7 of the treatment schedule. A small reduction in tumor volume compared to vehicle control has also been reported in other studies that utilized low dose doxorubicin experimental designs (Hossain et al, 2012; Lopez et al, 2009; Wang et al, 2013, 2010). …”
Section: Resultssupporting
confidence: 74%
“…The planned pairwise comparison of TUNEL staining in tumors from mice treated with DOX + PBS compared to DOX + iRGD was also not statistically significant ( t (15) = 0.435, p =0.670, a priori significance threshold = 0.05). Other studies that utilized a similarly low dose of doxorubicin to reduce side effects, also reported small reductions in tumor weight compared to vehicle control with minimal and not statistically significant changes in TUNEL staining (Hossain et al, 2012; Sugahara et al, 2015; Wang et al, 2010).
10.7554/eLife.17584.007Figure 4.TUNEL staining of mouse tissues.Mice bearing orthotopic 22Rv1 human prostate tumors were intravenously injected with PBS alone (PBS), 1 mg/kg DOX and PBS (DOX + PBS), or 1 mg/kg DOX and 4 µmol/kg of iRGD (DOX + iRGD).
…”
Section: Resultsmentioning
confidence: 95%
“…In combination, aspirin and doxorubicin resulted in enhanced effects in inhibiting tumor growth, arresting cell cycle and causing apoptosis in vitro when compared to single treatments. Combination therapy also resulted in synergistic antitumor activity in the xenograft model in nude mice 63. Others have shown that varied concentrations of aspirin,64 metformin,65 and heparin66 have shown efficacy in treating cancer when given in conjunction with chemotherapy.…”
Section: Combination Therapy: Targeted Multimodality Approach To Breamentioning
confidence: 95%